Perspektif Mahasiswa Keperawatan Tentang Kompetensi Keselamatan Pasien - Ike Puspitaningrum; Sukma Diani Putri; Evi Supriatun; Sally Yustinawati Suryatna; Nafisah Itsna Hasni (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Nursing students need to have adequate competence related to patient safety. Patient safety is a system aimed at providing safe healthcare services, preventing incidents for patients, and improving patient services. Knowing students' perspectives is necessary to understand how they think in response to what they have done or learned about patient safety. It is critical to evaluate nursing students' perspectives on patient safety competency and assess their level of competence. The results can be used to formulate plans to improve students' proficiency in patient safety among healthcare professionals. The design of this research is descriptive, with 108 respondents participating in filling out the Patient Safety Survey (PSS) instrument. The research results analyze students' competencies in three domains, namely patient safety review, patient safety issues, and incident reporting. The analysis results show that in the domain of patient safety review, 79.63% of respondents have a good perspective. In the domain of patient safety issues, 71.30% of respondents had a good perspective. Similarly, in the incident reporting domain, the majority of respondents also had a good perspective, which was the highest among the other domains, at 83.33%. Overall, it can be concluded that the survey results indicate that the respondents have a good perspective, with 82 respondents out of a total of 108 respondents (75.93%). Students who have attended patient safety management lectures and completed clinical nursing practice have good competence in patient safety. Future research is expected to be conducted in various cultural and contextual backgrounds to enhance the understanding of variables that influence patient safety in nursing practice and education